Digital Transformation of the High-Technology Manufacturing: An Overview of Main Blockades - Pasupuleti, Mahesh Babu; Adusumalli, Harshini Priya (American Journal of Trade and Policy, 2018)
Quality of life is linked to a country’s or region’s economic progress. Recent academic research has found that the pace of digitalization of the economy and society is similar. Despite this, there is evidence of low digital/advanced manufacturing technology adoption preparedness across economic sectors, despite government assistance and senior manager strategic orientation. The research aims to measure industry and organizational readiness for digital/advanced manufacturing technology adoption. An expert poll conducted by the author’s revealed low industrial readiness for digital/advanced manufacturing technology. As a result, the research focuses on identifying organizational digital transformation hurdles. An examination of academic literature and digital maturity assessment frameworks revealed a paucity of criteria for evaluating barriers. The project seeks to establish a method for evaluating digital transformation barriers. A questionnaire developed using analytical research measures an overall digital-transformation barrier level for a manufacturing firm and identifies issue areas. The power engineering company has a lower barrier level, which aligns with the engine construction and turbine engineering industries’ higher degrees of readiness to use digital technology. This finding validates the author’s method’s reasonableness.